(3HOGFY GdRghQ aj hbGFY GdOghQs - (3eMeO Hf CMeO Hf EjGS GdMfaj GdeUQj, CHh GdHQcGJ,J (B930 (3g` s
(3ChdgG (B:s
(3Chbd GfXQ deG CdaJ ajg aYd ce Chd JGQc YdekG GdPi Nda s
(3BNQgG (B:s
(3hPdc ai ehVYg hGd GdGeQ Edi Gf NdY ef GdSdWg , hJSdWf HYOg bGfUhg GdZhQi GfJgi s
(3GdehLhO efg eLdO jHJOF HPcQ SdWfI Gdedc GdCTQa EjfGd GdYdGFis
(3GfXQ CjkVG ef GdJGQjN Qbe (B78s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B236s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B295 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B42 s
Keywords: (3GdJGQjNs